Broadening, Tuning, and Tailoring of Passbands in RF Window for Multi-Frequency Vacuum Electron Devices - Sharan Singh A.; Thottappan M. (My University, 2025)
RF window maintains vacuum sealing as well as it provided maximum RF power transmission with minimum reflections at/in a desired frequency/frequency regime (passband). Passband tailoring is needed to suffice the operation of multi-frequency vacuum electron devices (VEDs). To accommodate the multiple frequencies broadening and tuning of the passband is investigated. Broadband RF window cannot pass the RF power, which is developed and propagated at the different distant frequency for multi-frequency gyrotron. A quad frequency RF window is designed for multi-frequency operation of gyrotron. A diamond window provides the accurate formation of passbands with negligible reflectivity (in order of 10-4) at desired frequencies. © 2020 IEEE.